NEW IN THE PATELLA FRACTURES TREATMENT - Hijazin, V.H.; Solod, E.I.; Abdulkhabirov, M.A.; Karpovich, N.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Medit͡s︡ina, 2018)
In the literature there is a gap of publications about patella fractures management which is due to the absence of serious attention to the injuries of this largest sesamoid bone. In addition, in the world literature there is a lack of monographs and toolkits for the treatment of patients with these injuries, furthermore, in textbooks and traumatology manuals there are only a few template recommendations to the tactics of treating patients with this trauma. Meanwhile, patella fractures represent approximately 0.5-1.5% of all fractures, delayed union, formation of a false joint, and the emergence of patellofemoral arthrosis after these fractures is not uncommon. In the scientific literature on traumatology there is no unified, all-recognized classification of these fractures, which hinders the development of a single algorithm for the treatment of patients with patellar fractures. There are no contradictory views to the treatment of patella fractures without displacement; however, in relation to the treatment of patients with complex patella fractures, there are divergent views between the fracture fragments preservation to partial or even total patellectomy. In connection with the foregoing, We considered the issue of treating patients with patella fractures topical. Based on a thorough analysis of treatment results of 113 patients we provided a working classification based on the number of patellar fracture fragments (two-fragmentary, three-fragmentary, four-fragmentary, multi-fragmentary, upper and lower pole fractures). Based on this classification, traditional, modified and new methods of treating patients with patellar fractures were used. This is described in more detail in the forthcoming article.